QUALITY OF LIFE AND DEPRESSION AMONG YOUNG PATIENTS SUFFERING FROM ACNE - Haroon, Muhammad Zeeshan; Alam, Aftab; Ullah, Ihsan; Ali, Rashid; Taimur, Muhammad Faridullah; Raza, Kainat (Journal of Ayub Medical College Abbottabad, 2019)
Background: In addition to depression, acne has considerable negative effects on the quality of life (QOL) which is estimated to be equal to that reported by patients with other chronic diseases. The immense suffering of ace patients both terms of depression and deterioration in quality of life and subsequent compromised social, vocational and academic performance makes them seek professional help more often for non-cutaneous manifestations e.g., poor body image, anxiety, depression etc. This study was conducted to determine the prevalence of depression and status of quality of life in acne patients visiting outpatient dermatology. Methods: This was a cross-sectional study conducted in the outpatient dermatology department of Ayub Teaching Hospital, Abbottabad between January and August 2018. The 74 consecutive acne cases visiting the dermatology OPD during the study period between the ages of 13 and 30 years were assessed for depression and QOL. Data was collected by Dermatology life quality Index (DLQI) and Patient Health Questionnaire (PHQ 9). Results: The ages of acne patients ranged between 14 years to 28 years with a mean age of 21.6 ±3.034 years. Majority 49 of the acne patients (66.2%) were female. Mean DLQI was 59±5.38. Of the total, 9 (12.2%) acne patients had no effect on the quality of life, 23 (31.1%) had small effect, 23 (31.1%) had moderate effect, 18 (24.3%) had large effect and 1 (1.4%) had extremely large effect on their quality of life. Mean PHQ-9 scale score was 7.72±4.93. Six (8.1%) acne patients were categorized as having no depression, 17 (23%) had minimal depression, 25 (33.8%) were having mild depression, 18 (24.3%) were moderately depressed and patients with moderately severe depression constituted only 8 (10.8%) acne patients. Conclusion: Acne is associated with depression and deterioration in QOL, which are more pronounced in teens and women. Keywords: Acne; Depression; Quality of Life; Psycho-dermatology